FeCl3-Induced Oxidation of POME for Efficient Treatment: An Experimental Study - Md Ali, Mohd Hafiz; Jalil, Mohammad Noor; Mohd Zain, Zainiharyati; Chay, Tay Chia; Mohd Zaki, Hamizah (International Journal of Sustainable Construction Engineering and Technology, 2024)
POME is a biomass waste product from cooking oil in the food industry which requires well treatment before discharge to the main stream. It becomes problematic cause POME contains a lot of organic compounds, suspended solids, lipids, and others which is hazard. Proper treatment is necessary in order to avoid adverse effects on the aquatic and fresh water quality. As that concerned, FeCl3 was introduced to initiate the oxidation reaction and indirectly to degrade the organic compounds in the POME. Throughout the experiment, 0.005 M of FeCl3 solution was mixed into each untreated POME. Besides POME, Glucose and lignin has been used for comparative study. Since POME is biomass waste, UV-Vis Spectroscopy instrumentation is the best to characterize the degradation behavior of organic compounds contained in POME, as well as in glucose and lignin. Based on Lamda, ? Max, the absorbance value as the indicator to measure the degradation level. The experiment done in room temperature (±25 °C) and catalyst optimization was done by Cyclic Voltammetry, CV with potential window from -0.1 to 1.5 V and for UV-Vis spectroscopy, the wavelength(nm) range between 200-600 nm was set throughout the analysis.